Analysis of Psychotropic Drug Utilization in Patients With Organic Mental Disorders - Yuliawati, Yuliawati; Sofyan, Indah Sri Wulan; Sadli, Nurul Kamilah; Kasmadi, Fathnur Sani (Sciences of Pharmacy, 2026)
Organic mental disorders are psychiatric conditions caused by identifiable brain pathology or specific systemic diseases, characterized by psychotic, affective, anxiety, and cognitive symptoms that can impair daily functioning. Psychotropic medications play a central role in their management; however, data on utilization patterns, particularly among outpatients in regional psychiatric hospitals, remain limited. This study aimed to quantitatively evaluate the use of psychotropic drugs using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method recommended by the World Health Organization, and to identify drugs within the Drug Utilization 90% (DU90%) segment to support rational drug use. This retrospective descriptive study utilized secondary data from medical records of outpatients diagnosed with organic mental disorders at Kolonel H. M. Syukur Regional Psychiatric Hospital, Jambi, in 2024, with a total sampling of 100 patients. The results showed that the total psychotropic drug utilization was 9.89 DDD per patient per day. Antipsychotics were the most frequently used class, followed by antidepressants and anxiolytics. The DU90% segment consisted of eleven drugs, predominantly atypical antipsychotics, selective serotonin reuptake inhibitors (SSRIs), and benzodiazepines, with olanzapine, escitalopram, fluoxetine, and alprazolam being the most commonly prescribed. Most patients were male, in the productive age group, and diagnosed with unspecified organic mental disorders. Overall, the pattern of psychotropic drug utilization reflects the complexity of clinical manifestations in organic mental disorders and underscores the importance of monitoring drug use to promote rational prescribing practices in clinical settings.